Kryterium fiskalne a procedura nadmiernego deficytu wobec Polski - Ancyparowicz, Grażyna; Stanisławski, Miłosz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The formulation of the nominal convergence criteria in the Treaty establishing the European Union was dictated by the need to examine the degree of consistency in the economies of Member States. These criteria enabled verification of their readiness to participate in the Monetary Union. In particular, establishment of the fiscal criterion was aimed to impose financial discipline. Poland participates in the third stage of Economic and Monetary Union on the rights of the State with a derogation, however, it does not exempt our country from fulfilling the fiscal criterion. Exceeding the reference level of the general government sector’s deficit triggered EC’s initialization of Excessive Deficit Procedure (EDP) against our country in 2009. The answer to this challenge was the Government’s plan to consolidate public finances. In 2011, at the cost of raising tax rates and eliminating most of the allowances, while limiting transfers to Open Pension Funds (OFE) and reducing social spending, an improvement of the reference indicators was achieved. Nevertheless, the results after the first quarter of 2012 are not optimistic.